The wonder of cloacal creation from myth to MONA - Heekeren, Deborah Van (Journal of religious and political practice, 2017)
This article builds on Michael Scott's reflections on wonder and its relationship to cosmology, ontology and anthropology. It is concerned with a category of origin myths that express the wonder of creation and which have been widely analysed in Freudian terms. Rather than lend weight to a psychoanalytic perspective, I want to explore possibilities for adding wonder to our conceptual toolkit. Myths are generally considered from within the purview of religion and magic, and studies of them focus on so-called primitive or ancient societies. I take the position that all belief systems, religious and non-religious, have foundational myths that are taken as truth and thus influence people's lives. Origin myths qua myths have conventionally been thought of as either literal or allegorical explanations for how an entity has come into existence. The wonder of creation is first experienced, then thought, and then explained away; by science, a god, an ancestor, or a dream. I want to reclaim existence as a wonder and suggest that art and poetry have a role to play in such a project. Further, an existentialist approach to myth might recover the wonder that is hidden by cause and effect modes of thinking.